Understanding Medicare-related decision-making by older adults: Role of technology support - Hye Soo Lee; Raksha A. Mudar; Wendy A. Rogers (Human Factors in Healthcare)
Medicare is a federal health insurance program with important public health implications for the older U.S. population. Thus, it is critical to support older adults in making informed decisions about Medicare plan enrollment. We conducted a narrative review of the research literature on Medicare knowledge, decision-making, and technology utilization for healthcare decisions by older adults to identify their need for support. We found that older adults had varying degrees of Medicare knowledge, which was mostly obtained from other people (e.g., friends, insurance brokers). Although assistive technology tools such as the Medicare.gov website and Medicare Plan Finder are available, older adults considered these tools difficult to use. As cognitive abilities, strategies, and the amount of information presented are associated with decision-making qualities, we suggest offering training on decision-making and technology use and using more inclusive website designs. Also, older adults’ characteristics and preferences in decision-making, such as stress avoidance and the need for reassurance, should be carefully considered. We have provided implications for both research and policy that emerged.